Polymeric Quaternary Ammonium Compounds: Versatile Antimicrobial Materials - L. Zubris, Deanna; P.C. Minbiole, Kevin; M. Wuest, William (Current Topics in Medicinal Chemistry, 2017)
Polymeric Quaternary Ammonium Compounds (polyQACs) comprise a broad class of materials with applications in medical implants, food processing, and surface sanitizing, amongst many others. These polymeric substances are especially promising due to their potent antibacterial activity and limited hemolytic toxicity. In particular, many polyQACs have superior therapeutic indices and a lower likelihood of developing antibacterial resistance in comparison to their monomers, making them ideal materials for wound dressings, catheters, and other biomedical applications. This review outlines the history and development, previous successes, current state of the research, and future directions of polyQACs in society.
Keywords: Antimicrobial activity